2019
DOI: 10.1111/soin.12331
|View full text |Cite
|
Sign up to set email alerts
|

Does the Association between Religiosity and Substance Use Vary between Adolescence and Early Adulthood?

Abstract: The present study examines whether the association between substance use and two dimensions of religiosity—institutional and personal—changes as individuals transition from adolescence to early adulthood. Using data from the National Longitudinal Study of Adolescent to Adult (Add) Health, logistic regression models with interaction terms were run to test the hypothesis that the association between an individual's religiosity and his or her level of substance use is stronger during early adulthood compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…As with overall health, lower levels of smoking and drinking were observed only for people who maintained steady religious practice between early life and midlife. Prior studies suggest that the negative association between religiosity and negative health behaviors grows stronger as individuals progress from adolescence to young adulthood (Freeman 2019). The results from the current study extend this observation into middle age and reiterate that early-life religious exposure is not sufficient to reduce the risk of later negative health behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with overall health, lower levels of smoking and drinking were observed only for people who maintained steady religious practice between early life and midlife. Prior studies suggest that the negative association between religiosity and negative health behaviors grows stronger as individuals progress from adolescence to young adulthood (Freeman 2019). The results from the current study extend this observation into middle age and reiterate that early-life religious exposure is not sufficient to reduce the risk of later negative health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent participation in formal religious activities connects individuals to a community of believers who may encourage less risky coping mechanisms to deal with stress and who may impose sanctions on those who violate health norms (Koenig et al 2012). Comparisons of the influence of religiosity on substance use across the transition to adulthood suggest that the protective effect of religiosity is stronger in early adulthood than adolescence (Freeman 2019). By early adulthood, religious individuals appear to have fully understood and internalized religious requirements to treat the body as a “sacred” instrument to be used in service to God.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of research that addresses the relationships between religiosity, future orientation, self-control, and delinquency, I examined the effect of religious service attendance and importance of religion on future orientation, self-control, and marijuana use. Because there is a substantial body of research that focuses on the relationship between religiosity and substance use (e.g., Freeman 2019;Guo and Metcalfe 2019;Hill and Pollock 2015;Hoffmann 2014;Jang 2019;Jang et al 2008;Longest and Vaisey 2008;Nie and Yang 2018;Rivera et al 2018;Thomson 2016;Varma et al 2017), and because previous research suggests that religiosity is more strongly related to substance use than serious delinquency (Burkett and White 1974;Miller and Vuolo 2018), I chose to focus on adolescent marijuana use. Based on previous research, I expect that adolescents who attend religious services frequently, and those who believe that religion is important, will be less likely to use marijuana.…”
Section: Current Studymentioning
confidence: 99%
“…Over the past half century, numerous cross-sectional and longitudinal studies have shown that people who are more religious tend to exhibit healthier smoking beliefs and behaviors than their less religious counterparts (Benjamins & Buck, 2008 ; Clark et al, 1999 ; Degenhardt et al, 2007 ; Ford & Hill, 2012 ; Freeman, 2021 ; Garrusi & Nakhaee, 2012 ; Gillum, 2005a , 2005b , 2021 ; Gottlieb and Green, 1984 ; Gryczynski & Ward, 2011 ; Hill et al, 2006 ; Holt et al, 2015 ; Idler & Kasl, 1997 ; Karvinen & Carr, 2014 ; Kendler et al, 2003 ; Koenig et al, 1998 ; Koenig & Vaillant, 2009 ; Koenig et al, 2012 ; Mahoney et al, 2005 ; Nonnemaker et al, 2003 , 2006 ; Parfrey, 1976 ; Strawbridge et al, 1997 , 2001 ; Stylianou, 2004 ; Wallace & Forman, 1998 ; Wang et al, 2015 ; Ward et al, 2014 ; Whooley et al, 2002 ; Yong et al, 2009 ). Although previous research has emphasized the role of religious attendance, additional protective effects have been observed for religious identities (specific religious groups), private forms of religious behavior (prayer and scripture study), personal orientations and experiences with respect to religion and the divine (intrinsic religiousness, religious salience/importance, positive religious coping, divine relations, and spirituality), and various composite measures of general religiosity.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these basic patterns, the results are somewhat murky. According to some studies, Protestants (generally), evangelical Protestants (e.g., Baptists, Pentecostals), Black Protestants, and Orthodox Christians are less inclined to smoke than other persons (Cartwright, 2021 ; Degenhardt et al, 2007 ; Freeman, 2021 ; Wasserman & Trovato, 1996 ). However, other studies deviate from these findings.…”
Section: Introductionmentioning
confidence: 99%